2001
DOI: 10.1046/j.1365-2958.2001.02205.x
|View full text |Cite
|
Sign up to set email alerts
|

Type 1 fimbriae deliver an LPS‐ and TLR4‐dependent activation signal to CD14‐negative cells

Abstract: SummaryFimbriae target bacteria to different mucosal surfaces and enhance the inflammatory response at these sites. Inflammation may be triggered by the fimbriae themselves or by fimbriae-dependent delivery of other host activating molecules such as lipopolysaccharide (LPS). Although LPS activates systemic inflammation through the CD14 and Toll-like receptor 4 (TLR4) pathways, mechanisms of epithelial cell activation by LPS are not well understood. These cells lack CD14 receptors and are unresponsive to pure L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
109
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 118 publications
(115 citation statements)
references
References 41 publications
6
109
0
Order By: Relevance
“…On the other hand, the first cells with which the HSV-2 virions come in contact and establish infection are the vaginal epithelial cells. Previous studies have demonstrated that certain TLRs are expressed by epithelial cells lining various body cavities (35)(36)(37)(38), and pathogen recognition by the stromal cells can result in inflammatory responses after bacterial stimulation (39,40). We hypothesized that viral recognition by stromal cells might contribute to the development of the adaptive immune responses.…”
Section: Tlr Recognition Of Viral Infection By Hematopoietic and Stromentioning
confidence: 97%
“…On the other hand, the first cells with which the HSV-2 virions come in contact and establish infection are the vaginal epithelial cells. Previous studies have demonstrated that certain TLRs are expressed by epithelial cells lining various body cavities (35)(36)(37)(38), and pathogen recognition by the stromal cells can result in inflammatory responses after bacterial stimulation (39,40). We hypothesized that viral recognition by stromal cells might contribute to the development of the adaptive immune responses.…”
Section: Tlr Recognition Of Viral Infection By Hematopoietic and Stromentioning
confidence: 97%
“…Thus, our data do not currently dissipate the debate that exists concerning the expression and role of CD14 in LPS-induced lung epithelial activation. Several authors proposed that these cells are CD14-negative (39,40), while others demonstrated both CD14 mRNA and cell surface protein in human airway epithelial cells (2,18,19). In fact, these contradictory results may be explained by distinct basal activation or differentiation state of the epithelial cells used throughout these investigations.…”
Section: Fig 7 Activation Of Pulmonary Epithelial Cells By Lps Invomentioning
confidence: 99%
“…Epithelial cells must be protected from constant TLR activation by commensals and their PAMP, in order for mucosal integrity to be maintained. The epithelial cells thus lack co-receptors like CD14 [6][7][8][9][10][11], and in addition, commensals have been suggested to actively suppress epithelia responses through NF-jB [12,13]. Yet, mucosal pathogens evoke rapid TLR4-dependent responses at mucosal sites, suggesting that alternative ligands and receptors might be involved in mucosal TLR activation.…”
Section: Introductionmentioning
confidence: 99%